Hemorrhagic Complications of Minimally Invasive Urological Surgeries, Treated with Selective Endovascular Embolization - Sarel Halachmi; Amos Ofer; Eduard Gershin; Ahuva Engel; Shimon Meretyk (The Scientific World Journal)
Minimally invasive urological procedures have gained in popularity and replaced open surgery in various urological procedures. Although considered minimally invasive, these procedures are not free from complications, and life-threatening hemorrhage may occur. Herein we describe 3 case series of patients who underwent minimally invasive urological surgeries that were complicated with bleeding. In all 3 patients we used super selective angiographic embolization to stop hemorrhage. Minimally invasive urological surgeries carry the risk of hemorrhage, and patients should be informed about this possibility. In hemodynnmic stable patients endovascular embolization allowed bleeding cessation with maximal preservation of the bleeding kidney tissue.